SOLUTION: Solve the system by graphing. 3x + y = 6 3x – y = 0
-> SOLUTION: Solve the system by graphing. 3x + y = 6 3x – y = 0
solves your algebra problems and provides step-by-step explanations!
: algebra software solves algebra homework problems with step-by-step help!
Algebra: Graphs, graphing equations and inequalities
Click here to see ALL problems on Graphs
Solve the system by graphing.
3x + y = 6
3x – y = 0
put this solution on YOUR website!
3X+Y=6, Y=-3X+6 (RED LINE)
3X-Y=0, -Y=-3X, Y=3X (GREEN LINE)
(graph 300x200 pixels, x from -6 to 5, y from -10 to 10, of TWO functions y = -3x +6 and y = 3x).